Rapid kinetics of serum IgA after vaccination with Prevnar®13 followed by Pneumovax®23 - Rebecca R. Crowther; Christine M. Collins; Cheryl Conley; Osvaldo J. Lopez (Heliyon, 2017)
Streptococcus pneumoniae is a causative agent of community-acquired pneumonias. The recommendations of the 2012 Advisory Committee on Immunization Practices include vaccination with Prevnar®13 (protein-polysaccharide conjugate vaccine; PCV), followed by Pneumovax®23 (polysaccharide-based vaccine; PSV) in adults 65+ or the immunocompromised. In this experiment, a group of 4 healthy volunteers were vaccinated with PCV followed by PSV 60 days later. ELISAs were optimized to study kinetics of IgA, IgM, total IgG and its four subclasses against 14 polysaccharides of the pneumococcal capsule. Although this is a small sample, results from volunteers consistently showed that rapid induction of monomeric IgA followed by rapid decline is typical for both vaccines. IgA was not detected after PSV vaccination in those serotypes present in PCV, suggesting the population of B cells secreting IgA is not renewed within 60 days of activation by PCV. In contrast to mice, human neutrophils expressed a functional receptor for the constant region of monomeric IgA. Thus, the role of IgA early in the human immune response should be further investigated.